2010
DOI: 10.1583/09-2877.1
|View full text |Cite
|
Sign up to set email alerts
|

Direct Videoscopic Approach to the Thoracic Aorta for Aortic Endograft Delivery: Evaluation in a Human Cadaver Circulation Model

Abstract: A direct videoscopic approach to the descending thoracic aorta proved a feasible technique for branched endograft delivery to the aortic arch and abdominal aorta in a human cadaver model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…using coaxial sheaths, transapical access, transapical-femoro “body floss” wire. 2125 Adopting these alternative strategies for proximal advancement of the endograft into the aortic arch is, however, associated with several concerns about the safety of these approaches. 26 Early or late complications, such as an apex or ascending aortic bleeding, coronary artery lesions and pseudoaneurysms can occur.…”
Section: Discussionmentioning
confidence: 99%
“…using coaxial sheaths, transapical access, transapical-femoro “body floss” wire. 2125 Adopting these alternative strategies for proximal advancement of the endograft into the aortic arch is, however, associated with several concerns about the safety of these approaches. 26 Early or late complications, such as an apex or ascending aortic bleeding, coronary artery lesions and pseudoaneurysms can occur.…”
Section: Discussionmentioning
confidence: 99%
“…For the former, chimney grafts have shown promising midterm results in the preservation of supra-aortic branches during aortic arch TEVAR. 9 For introduction and deployment of the stent-graft, there are several maneuvers to overcome access issues raised by aortic tortuosity, 7,8,10 which is usually severe in large thoracic aneurysms. 6 Among the maneuvers attempted in our case, coaxial sheaths allowed cannulation of the aortic arch, but accurate insertion of the endograft was not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been suggested to overcome access and stability issues when dealing with tortuous aortic anatomy, including the use of stiff “buddy wires” from the contralateral femoral artery, coaxial sheaths, and open or videoscopic assistance to straighten the tortuous thoracic aorta, as well as the through-and through guidewire manuever. 7,8…”
Section: Introductionmentioning
confidence: 99%
“…Alternative access techniques have been described, including conduits to the iliac arteries and infrarenal aorta, as well as to the descending thoracic aorta. 2,3 MacDonald et al first described TEVAR through the apex of the left ventricle in a single report in 2009, using a Gore TAG (W L Gore and Associates, Flagstaff, AZ, USA) thoracic endoprosthesis in a patient with a ruptured pseudoaneurysm of the aortic arch and Szeto et al reported transapical TEVAR in a patient with a large pseudoaneurysm of the ascending aorta using a Zenith TX2 endograft (Cook Europe, Bjaeverskov, Denmark). 4,5 This new technique may be indicated in patients with life-threatening thoracic aortic pathologies, that can neither receive open nor endovascular repair from a downstream access site.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative access techniques have been described, including conduits to the iliac arteries and infrarenal aorta, as well as to the descending thoracic aorta. 2,3…”
Section: Introductionmentioning
confidence: 99%